Desarrollo de una herramienta ofimática para el seguimiento de cuentas médicas de la IPS Otorrinolaringólogos Asociados de Córdoba, OTOC S.A.S. (2023)
The process of invoicing and filing of accounts is responsible for maintaining the financial information of health organizations for their economic sustainability. The Institution Providing Health Services (IPS) Otorrinolaringólogos Asociados de Córdoba (OTOC) S.A.S. of the city of Montería, presented some inconsistencies in the reception of supporting documents and in the filing of accounts, therefore, it is necessary to have an instrument that allows the timely follow-up of medical accounts. The objective of the business practice is to develop an office automation tool for the follow-up of medical accounts of the IPS OTOC S.A.S. of Montería, Córdoba. The methodology is descriptive with a quantitative approach; the observation technique was used. Likewise, the current regulations and the files of medical accounts were taken into account to develop the office automation tool for follow-up, which was pilot tested with two medical accounts of the patients treated at the IPS. Computer equipment with Microsoft Excel, tape recorder and stationery were used. The design of the office automation tool for the follow-up of the medical accounts was achieved with the support of the Unit's personnel to validate it, considering the elements that the electronic invoice of the IPS has. These elements include the IPS's NIT, the provider's code, address, telephone, and e-mail. After the IPS information is the invoice date, invoice due date and payment method; it also contains the EPS and patient information, which starts with the entity, the NIT, the EPS address, telephone, patient name, identification, date of birth of the user, date of admission, date of discharge, the contract that was agreed with the IPS, the fee for services rendered, type of affiliation, patient age, regimen and admission. Finally, the service code, manual, description of the service, quantity, unit value, total subtotal value, discount, VAT, co-payment, co-payment, co-moderation fee, copayment and total to be paid. During the pilot test carried out with the two electronic invoices of the IPS, it has been decided to add 6 elements to the office automation tool for tracking medical bills. These elements are the following: date of the finding, inconsistency found, unit responsible for the inconsistencies, date of the corrective action, corrective action, and unit responsible for the corrective action. The purpose of this addition is to facilitate the follow-up of medical accounts that present inconsistencies during the billing process. The office automation tool will allow timely action for the proper handling of accounts in the billing and filing process.